HADIS MENJILATI JARI SETELAH MAKAN PERSPEKTIF MA’AN AL-HADITH - Riri Rizqiyatul Falah; Hartati Hartati; Lukman Zain MS (IAIN Syekh Nurjati Cirebon, 2019)
Differences editorial in a hadith theme are possible, one of which is in the tradition licking fingers after eating. In the theme of the hadith there are 2 very prominent editors, namely in the form of a sentence kalimat يَلْعَقَهَا اَوْ يُلْعِقَهَاor only use the word يَلْعَقَهَا both of them are fi'il muda>ri’. But there is also the Hadith use the word mad لَعِقَ which is fi'il madi. The word يُلْعِقَهَا in the matan editor means 'licking fingers to others'. At first glance maybe the message of the Prophet Muhammad. in the hadith strongly recommends licking your fingers after eating, but whether to ask for help from others to do so. This paper aims to find out the analysis of ma’an al-hadith with an effort to trace the meaning of licking fingers after eating.